Media reporting patterns in Europe - Zografova, Yolanda (Javnost (Ljubljana), 2012)
This article presents a study of the semantic construction of Europe reflectedby leading print and broadcast media in 14 EU member countries. Are there any significant differences between the representations of media in the old and new EU member states? Did the media in both country groups succeed in achieving semantic integrity with regard to representation of key issues and challenges facing the "new" Europe of citizens? Based on analyses of print and broadcast media news on the themes of "construction of Europe" and "Reform Treaty" during the period May-October 2008, significant tendencies are comparatively outlined. Our findings suggest that there was a prevailing country-specific, instead of a unified pattern of media reporting. Furthermore, the classification of media actors by country type (old, new and non-EU members' media) also proved to be a significant, though a weaker determinant of both thematic interest and discursive structure of the mediated European public sphere in comparison with the country of the media.
Keywords: Europe; Evropa; mass media; množični mediji; informiranje; vplivi; javna sfera; javnost